Training in the Initial Range of Motion Promotes Greater Muscle Adaptations Than at Final in the Arm Curl - Gustavo F. Pedrosa; Marina G. Simões; Marina O. C. Figueiredo; Lucas T. Lacerda; Brad J. Schoenfeld; Fernando V. Lima; Mauro H. Chagas; Rodrigo C. R. Diniz (MDPI AG, 2023)
Objective: The effects of ROM manipulation on muscle strength and hypertrophy response remain understudied in long-term interventions. Thus, we compared the changes in strength and regional muscle hypertrophy after training in protocols with different ranges of motion (ROM) in the seated dumbbell preacher curl exercise using a within-participant experimental design. Design and methods: Nineteen young women had one arm randomly assigned to train in the initial ROM (INITIALROM: 0°-68°; 0° = extended elbow) while the contralateral arm trained in the final ROM (FINALROM: 68°-135°), three times per week over an eight-week study period. Pre- and post-training assessments included one repetition maximum (1RM) testing in the full ROM (0°-135°), and measurement of biceps brachii cross-sectional area (CSA) at 50% and 70% of humerus length. Paired t-tests were used to compare regional CSA changes between groups, the sum of CSA changes at 50% and 70% (CSAsummed), and the strength response between the training protocols. Results: The INITIALROM protocol displayed a greater CSA increase than FINALROM protocol at 70% of biceps length (p = 0.001). Alternatively, we observed similar increases between the protocols for CSA at 50% (p = 0.311) and for CSAsummed (p = 0.111). Moreover, the INITIALROM protocol displayed a greater 1RM increase than FINALROM (p < 0.001). Conclusions: We conclude that training in the initial angles of elbow flexion exercise promotes greater distal hypertrophy of the biceps brachii muscle in untrained young women. Moreover, the INITIALROM condition promotes a greater dynamic strength increase when tested at a full ROM compared to the FINALROM.